The effectiveness of live streaming commerce in driving consumer engagement and purchasing intention - Leong, Ze Qi (2025)
The rapid proliferation of live-streaming commerce has revolutionized e-commerce by driving consumer engagement and purchasing intention. This study explores the effectiveness of live streaming platforms in influencing consumer behaviour, with a focus on broadcasters’ roles, real-time interaction, and psychological mechanisms that reduce perceived uncertainty. Employing signalling theory and consumer motivation theory, the research examines dual routes through which broadcasters impact consumers: product-centred and social-interaction centred routes. Findings reveal that broadcasters' physical characteristics and personal values serve as critical signals to build trust and improve product fit perceptions, ultimately enhancing purchase intention. Besides, to support the hypothesis by evidence, this research will conduct a online questionnaire to collect primary data and prepare to analysis. The target will be located to young adults and undergraduate level students and above in University Tunku Abdul Rahman’s campus in Malaysia Moreover, the result will be interpreted to justify the research objectives and problems that may provide some acknowledge on live-streaming commerce categories in the future.